2016
DOI: 10.1016/j.phrs.2016.02.028
|View full text |Cite
|
Sign up to set email alerts
|

PPARγ signaling and emerging opportunities for improved therapeutics

Abstract: Peroxisome proliferator-activated receptor gamma (PPARγ) is a ligand-activated nuclear receptor that regulates glucose and lipid metabolism, endothelial function and inflammation. Rosiglitazone (RGZ) and other thiazolidinedione (TZD) synthetic ligands of PPARγ are insulin sensitizers that have been used for the treatment of type 2 diabetes. However, undesirable side effects including weight gain, fluid retention, bone loss, congestive heart failure, and a possible increased risk of myocardial infarction and bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
105
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(123 citation statements)
references
References 141 publications
4
105
0
3
Order By: Relevance
“…To verify the known insulin-sensitizing effect of thiazolidinediones, we assessed the effects of rosiglitazone treatment on body weight and fasting or challenged blood glucose levels in the mice. As given in S4 Fig, we observed a significant increase in body weight upon rosiglitazone treatment (S4A Fig), which is a well-known side effect of PPARγ agonists [40]. In line, the insulin-sensitizing effect of rosiglitazone was reflected in reduced fasting blood glucose levels (S4B Fig) and an improved insulin sensitivity after oral glucose administration (S4C Fig).…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…To verify the known insulin-sensitizing effect of thiazolidinediones, we assessed the effects of rosiglitazone treatment on body weight and fasting or challenged blood glucose levels in the mice. As given in S4 Fig, we observed a significant increase in body weight upon rosiglitazone treatment (S4A Fig), which is a well-known side effect of PPARγ agonists [40]. In line, the insulin-sensitizing effect of rosiglitazone was reflected in reduced fasting blood glucose levels (S4B Fig) and an improved insulin sensitivity after oral glucose administration (S4C Fig).…”
Section: Resultssupporting
confidence: 71%
“…Here it is tempting to argue in favor of the well-known insulin-sensitizing effects of thiazolidinedones [40], which might preferentially account for the improved tissue repair in ob/ob mice rather than the attenuated inflammatory conditions at the wound site. However, this notion actually does not reflect the actual conditions at impaired wound sites.…”
Section: Discussionmentioning
confidence: 99%
“…During the pathogenesis of periodontitis, the mechanism for the absorption of alveolar bone involves in bone matrix damaged and bone cells invaded by bacteria, osteoclasts activation induced by inflammatory mediators, and the inhibition of bone formation (Henderson & Nair, ). RGZ can increase the sensitivity of insulin and was used as a treatment for type 2 diabetes (Wang, Dougherty, & Danner, ). Previous studies showed that the long‐term use of RGZ caused reduction in bone mineral density (Lecka‐Czernik, ) and elevated bone fracture rate (Choi, Park, & Choi, ), and proposed an underlying mechanism that RGZ promoted the activation of osteoclasts and inhibit osteoblast formation (Wan, ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, intracellular RHAMM protein isoforms complex with, sustain activity and regulate subcellular targeting of the MEK1/ERK1,2 complexes that affect adipogenesis [38]. Intracellular RHAMM also partners with anti-adipogenic proteins such as the ERK1,2 target protein ANKRYD26[39, 78], which results in suppression of the activation and expression of master adipogenic transcription factors such as PPARγ[79]. …”
Section: Discussionmentioning
confidence: 99%